Analisis Waktu Tunggu Resep Obat Instalasi Farmasi Di Rumah Sakit X Surabaya - Paramitha, Gladysia Kirana; Wiaya, Hermanto; Putri, Linta Meyla; Setiawan, Liman (Bagian Penelitian & Pengabdian Masyarakat STIKES Adi Husada, 2025)
Background: Waiting time is the length of time starting from when the patient submits a prescription until receiving the medicine according to the time limit, which is <30 minutes for non-compound prescriptions and <60 minutes for compound prescriptions. AIMS: The purpose of this study was to analyze the length of waiting time for drug prescriptions in the pharmacy installation at Hospital X Method: The method used is a descriptive analytical method to describe the reality that occurs with the variables studied and analyzed statistically. Results: Based on the results of the study, Hospital X has not reached the waiting time standard. The average waiting time for drug prescriptions in JKN patients is 64 minutes 70 seconds for compound prescriptions and 51 minutes 59 seconds for non-compound prescriptions. The constraints that occur regarding the hospital pharmacy computer system are computer system errors, especially the national BPJS error system. Because 70% of patients at Hospital X Surabaya are almost all BPJS patients. And there is no specific measurement regarding the speed and number of prescription targets to determine the speed of each employee in serving drug prescriptions. Conclusion: It is expected that hospitals will implement a target ratio of drugs that must be served by each employee to measure the extent to which pharmaceutical services can meet the target or standard for optimal drug administration for patients and can help the evaluation process of the length of waiting time for drug prescriptions.